Trait motivations of crowdsourcing and task choice: A distal-proximal perspective - Pee, Loo Geok (2018)
Research on crowdsourcing participation has identified the four primary motivators to be payment, job-market signaling, competence development, and fostering social affiliation. These motivators have mostly been understood in terms of the intrinsic-extrinsic perspective, and participation has been treated as a black box. This study extends understanding of the primary motivators by clarifying their differential effects in terms of the distal-proximal perspective of motivation, and distinguishing among participation in (i.e., choice of) unstructured tasks, high-commitment tasks, and interdependent tasks. Findings based on a survey of 283 crowdsourcing participants indicate that those motivated to develop competence (i.e., learn new knowledge and skills) tend to choose high-commitment tasks requiring more effort and therefore opportunities to improve ability, rather than focusing on task structuredness or interdependence. Those who are motivated to foster social affiliation tend to focus more on choosing highly interdependent tasks requiring coordination and collaboration with other participants. Those motivated by payment tend to focus on demonstrating competence relative to others and are therefore more likely to choose structured tasks with clear, comparable output. These findings enhance the conceptual clarity of different motivators, and inform crowdsourcing organizers on the motivator to focus on based on task characteristics.